Critical Review Journal Opportunities for Artificial Intelligence Development in the Accounting Domain: The Case for Auditing Melia A. Baldwin, Carol E. Brown, & Brad S. Trinkle (2006) - Muslimin; Nahwani Fadelan; Wahid Hasyim; Fitriah; Fithiyaturrahmah (CV Edujavare Publishing, 2026)
This critical review aims to analyze the article by Baldwin, Brown, and Trinkle (2006) titled Opportunities for Artificial Intelligence Development in the Accounting Domain: The Case for Auditing. The article discusses the opportunities for developing Artificial Intelligence (AI) in the accounting field, particularly in auditing and assurance processes. The method used in this review is a literature study with a descriptive-analytical approach to the article's content, covering research objectives, methods, main findings, contributions, as well as the strengths and limitations of the article. The review results show that auditing is a very potential field for AI application because it involves analyzing large amounts of data, complex decision-making, professional judgment, and anomaly and fraud detection. The authors of the article emphasize that AI is not intended to replace auditors, but rather serves as a tool to enhance efficiency, effectiveness. and the quality of audits. Although this article has limitations because it is conceptual and not yet supported by empirical evidence, the review provides an important contribution as an initial theoretical foundation for research on AI in auditing. Thus, this article remains relevant to be used as a reference in research on audit analytics, continuous auditing, fraud detection, and the use of AI technology in the accounting profession.